PENGARUH NHT BERBANTUAN PRAKTIKUM TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMP HARUNIYAH PONTIANAK - Lili Aprianti; Ifriany Harun; Lukman Hadi (Universitas Tanjungpura, 2019)
AbstractThe aimed of this study were to determine whether there was a significantdifference of motivations and achievements between students taught using NHT of cooperative learning type and conventional learning on topics such as acid, alkaline and salt and to determine the effect of NHT of cooperative learning type on students’ achievements. To this, nonequivalent control group design was adopted and instruments consisted of questionnaires and test were used to collect data. According to statistical analysis of motivations using u mann whitney test and achievements using t test, the propabilty score of motivations and achievements were 0,000 and 0,000 which meant that there was a significant difference of motivations and achievements between students on both groups. According to calculation, the score of effect size was 1,7 which meant that NHT of cooperative learning type had large effect on improvements of students’achievements. In conclusion, there was a significant difference of motivations and achievements between students taught using NHT of cooperative learning type and conventional learning and it also reveals that NHT of cooperative learning type has large effect on improvements of students’ achivements. Keywords:Acid Base and Salt, Learning Achievements, Motivation, NHT